2015
DOI: 10.2989/17280583.2015.1007866
|View full text |Cite
|
Sign up to set email alerts
|

Family accommodation mediates the association between anxiety symptoms in mothers and children

Abstract: These results inform theory and imply that the development of interventions designed to target family accommodation may improve the prognosis of those diagnosed with paediatric anxiety disorders and youth with subclinical anxiety symptoms by reducing both parent and child anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 46 publications
4
28
0
2
Order By: Relevance
“…Parental peripheral OT has been linked to parenting behavior, which in turn has been shown to influence the oxytocinergic system of infants, (Apter-Levy et al, 2013; Feldman et al, 2010b) and family accommodation has been found to mediate the link between anxiety in mothers and youth (Jones et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Parental peripheral OT has been linked to parenting behavior, which in turn has been shown to influence the oxytocinergic system of infants, (Apter-Levy et al, 2013; Feldman et al, 2010b) and family accommodation has been found to mediate the link between anxiety in mothers and youth (Jones et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…A study comparing child and mother ratings of family accommodation found that maternal anxiety moderates the link between the mother’s and child’s ratings, with more anxious mothers showing higher agreement with child ratings than less anxious mothers (Lebowitz et al 2014a, b). Another study by Jones et al (2015) directly examined whether family accommodation mediates the association between maternal anxiety and child anxiety and found significant mediation.…”
Section: Parent Behaviormentioning
confidence: 99%
“…This study also confirmed the positive correlation between levels of accommodation and severity of anxiety symptoms in the child. In yet another study of family accommodation in pediatric anxiety, Jones et al ., [42] using FASA, found that family accommodation mediated the relation between maternal anxiety and child anxiety.…”
Section: Family Accommodation In Anxiety and Other Disordersmentioning
confidence: 99%